Option Implied Dividends Predict Dividend Cuts: Evidence from the Financial Crisis. (May 2017) - Fodor, Andy; Stowe, David L.; Stowe, John D.
Abstract: We employ the forward‐looking implied dividend information contained in option prices to predict dividend cuts and omissions during the recent financial crisis. The large number of dividend cuts and omissions during the 2008–09 financial crisis period provides the opportunity to study the predictability of dividend cuts in a controlled environment. Implied dividends and implied volatility, based on put–call parity and computed from put and call option prices, prove to be effective in predicting those cuts, especially compared to only using the equity market and accounting variables conventionally used for this purpose. Options‐derived variables (implied dividends and implied volatility) enhance the ability to identify firms more likely to reduce or omit dividend payments.